Pengaruh Retail Mix Terhadap Keputusan Pembelian Pada Bali Cenik Kids Apparel di Denpasar - Anggraeni, Debbie Tri; Nurcahya, I Ketut (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
The existence of modern retail now increasingly entered in the daily activities of the community. This is due to a change in shopping patterns in society. Such changes affect the taste of consumers in making purchasing decisions. Purchasing decisions in a store can occur as a result of variable mix consisting of retail pricing, merchandising, promotion, service, location and atmosphere store outlets. The results based on multiple linear regression analysis showed that the retail mix simultaneously and partially positive and significant impact on purchasing decisions. Keywords: retail, retail mix, and purchasing decisions
Keywords: retail, retail mix, purchasing decisions